An analysis of different means of egress in selected hospitals in Quezon City - Dela Mines, Christian Neil R.
ABSTRACT The study aims to explore the different means of egress in the selected hospitals in Quezon City and examine if these are appropriate and sufficient to accommodate the various types of occupants inside the institutions in a fire situation. It employed a mixed method approach, specifically concurrent method, and data gathering methods such as survey, interviews and visual documentation. Three (3) hospitals were covered in the study. Purposive sampling was used to determine the fifteen (15) respondents from each hospital. For the interviews, three (3) key informants were chosen from the respondents using a stratified sampling to ensure that there were ambulant, semi-ambulant and non-ambulant informants. Findings of the study revealed that majority of the existing means of egress were inappropriate. The common violations of the egress routes included the widths of the egress, the placement of handrails and guardrails in both staircases and ramps and the condition (locked exits) and swing direction of doors. Other non-compliances involved the usage of the space underneath the interior stairs, and the riser and tread dimensions of exit staircases. Reasons for non-compliance included the conflicts between the guidelines of the Fire Code and National Building Code. Other reasons involved the lack of storage and hospital staff. Although majority of these egress routes were inappropriate, most of the institutions had sufficient number of fire exits except for Hospital C. Aside from the appropriateness and sufficiency of the existing means of egress, results of the study also showed that human psychology, specifically occupant awareness with the evacuation plan and behavior during emergencies, was also a critical factor that could affect the safety of the occupants during emergencies like fire. To strengthen the results of the study, it is recommended to conduct a more comprehensive analysis regarding the materials and construction of fire exits. Studies regarding external factors that could affect occupant safety, like overcrowding, are also highly suggested.